Influência da queima da palha de cana-de-açúcar na ocorrência de doenças respiratórias em diferentes localidades do Estado de Alagoas. - Almeida, Lucia Guiomar Basto Fragoso de (2008)
In the present study it was analyzed influence of the atmospheric pollution proceeding from the burning of the straw of the sugar cane-of-sugar on the respiratory illnesses Asthma, Pneumonia and Bronchitis, cities of São Miguel dos Campos, Matriz de Camaragibe and Penedo, in the state of Alagoas, the years of 2005 2007, through data collected of detention of focus of forest fires gotten for sensor AVHRR of the system of satellites NOAA. In this period the daily hospital internments for respiratory illnesses had been quantified, through data of the DATASUS. The climatologically normal gotten for Climatology Sector of the Centro de Ciências Agrárias CECA/UFAL , and collected rain data had been used in the study in the years studied for. Diretoria de Meteorologia da Secretaria de Estado do Meio Ambiente e dos Recursos Hídricos de Alagoas. Analyze them evidenced in contrast that of the joined one in literature, the sugar cane zone of the region possess you practice opposing agriculturists, therefore the observed period of the burning occurs when the temperatures start to raise themselves gradual while the relative humidity of air decreases. The morbidities appear during all year, however the months of bigger occurrence are in the period of winter, as seen in literature, previous studies observed an increase of these in the months most cold of the year, however in these periods they had not occurred to the burning of the straw of the sugar cane-of-sugar. In the studied cities, the focus of forest fires had been registered of August the April. The biggest values of these focus appear in January, February and November, In the peaks of Asthma São Miguel dos Campos are seen before and soon after the periods of bigger precipitations, that is, to the measure that the precipitations also increase the cases of Asthma raise. Good correlation of the polynomial type of 2ª order the morbidity presented in Matriz de Camaragibe was not sufficiently significant, also valley to point out that it in few months did not have registers during the studied years, showing that it can have occurred sub-notification making it difficult the correlation with the burning of the straw of the sugar cane-of-sugar. Some episodes had existed where the cases of internments precede precipitations and some times show proportional values inversely. In Penedo, the focus of forest fires always appear of continuous and constant form in the three years and in the months of November and January, registering of 1 the 5 focus. It is visible that the burning alone occurs really when of the lesser precipitation incidence How much to the presented morbidity, although the illness to disclose itself all during the year, the found values do not seem to have correlation with period of sugar cane-of-sugar burning. However it can be seen that the year of 2006 the illness was present with bigger intensity. It was observed that not the existence of a good relation between the variable.